Governance in the European Union - Marks, Gary, 1952- (SAGE, 1996)
Presenting a fresh alternative to traditional state-centred analyses of the process of European integration, 'Governance in the European Union' clearly shows the interaction of subnational, national, and supranational actors in the emerging European polity. This 'multilevel politics' approach offers a powerful lens for viewing the future course of European integration. The authors' empirical exploration of areas such as regional governance, social policy, and social movements underpins their broad conceptual and theoretical framework, providing significant new insight into European politics.